Photocatalytic Carbamoyl Radical Transfer to Alkenyl Azaarenes - Yu, Zi-xuan; Ma, Shi-Wei; Li, Guang-xun; Ma, Long-jun (Synlett, 2024)
1-Phenyl-3-azaarenyl-propan-1-amine structural moieties have been widely incorporated in pharmaceuticals and biologically active compounds; however, current synthetic methods to access these compounds need multiple steps and proceed with low efficiency. Herein, we reported an efficient photocatalytic carbamoyl radical transfer approach that allows the preparation of these compounds in high yields (up to 88%). The reaction easily runs on a gram-scale and was applied for the preparation of pheniramine in two steps with 72% total yield.
Keywords: azaarene; photocatalysis; carbamoyl radical; 1,4-dihydropyridine